2010
DOI: 10.1002/clc.20811
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Shock Wave Therapy Reduces Angina and Improves Myocardial Function in Patients With Refractory Coronary Artery Disease

et al.

Abstract: Background: Safe and effective therapeutic management of refractory coronary artery disease (CAD) in heart patients is critical to enhance cardiovascular function and improve quality of life. Current therapies for refractory CAD are inadequate in ameliorating angina and promoting revascularization of ischemic myocardium. Hypothesis: Cardiac shock wave therapy (CSWT) is a safe and effective noninvasive intervention in the management of patients with refractory CAD. Methods: The study enrolled 9 male patients ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 21 publications
(23 reference statements)
5
32
0
Order By: Relevance
“…Finally, perhaps the most compelling advantage of ESMT is its safety. As in previous studies, we did not observe any adverse effects from ESMT [1,12,13,16]. …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Finally, perhaps the most compelling advantage of ESMT is its safety. As in previous studies, we did not observe any adverse effects from ESMT [1,12,13,16]. …”
Section: Discussionsupporting
confidence: 88%
“…Our study extends the findings of previous studies, which have suggested that ESMT may be safe and efficacious in small groups of patients [1,7,9,12,13,16,28]. This is at present the first and largest international multicenter study showing that ESMT decreases nitroglycerin consumption, increases myocardial perfusion on SPECT, improves CCS scores, and increases exercise capacity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…[23] Following our initial report, several clinical studies with positive results were reported worldwide. [34][35][36][37] To confirm the usefulness and safety of our SW therapy, we performed a second clinical trial in a randomized and placebo-controlled manner. In this second trial, again we were able to demonstrate that the low-energy SW therapy not only improved symptoms and reduced nitroglycerin use, but also improved LV function ( figure 7), establishing cardiac SW therapy as an effective and safe angiogenic strategy for severe ischemic heart disease.…”
Section: Clinical Studiesmentioning
confidence: 98%
“…In vitro studies have demonstrated that ECSWT can enhance vascular endothelial growth factor (VEGF) mRNA expression in cultured human umbilical vein endothelial cells and in rat bone marrow cells (BMCs) as well as promote BMCs differentiation into cells with endothelial phenotype [3,4]. Swiss company STORZ MEDICAL developed the first extracorporeal cardiac shock wave apparatus MODLITH SLC in the world in 2003 [5]. In 2010, Kikuchi performed a double-blind placebo-controlled trial in patients with severe angina pectoris to further confirm the effectiveness and safety of ECSWT [6].…”
Section: Introductionmentioning
confidence: 99%